Strategie obrazowania historii w filmach Aleksandra Sokurowa - Pigulak, Marcin (My University, 2021)
Celem rozprawy doktorskiej Strategia obrazowania historii w filmach Aleksandra Sokurowa jest udowodnienie, że strona treściowa i formalna filmów rosyjskiego reżysera znajduje swoje źródło w intencji obrazowana zachodzących w historii procesów historycznych. Dzięki temu dorobek A. Sokurowa można rozpatrywać nie tylko jako autorską egzemplifikację sztuki filmowej, ale również jako przykład dyskursu z zakresu filozofii historii, a nawet historiografii (postrzeganej jako element kultury historycznej w interpretacji Jörna Rüsena). Autor wykazał, że reżyser wykorzystuje różnorodne strategie obrazowania przeszłości: „świadka swoich czasów” (zarówno poprzez prezentowanie subiektywnej perspektywy autorskiej, jak i opowiadanie o przeszłości z punktu widzenia naocznego uczestnika wydarzeń), „archiwozofa” (kształtującego narrację o przeszłości przez pryzmat archiwaliów), „biografa” (polemizującego z historiograficznym podejściem do procesów historycznych), a także narratora historii (odwołującego się do pojmowania historii w kontekście metafory).

The aim of the doctoral dissertation titled Strategy of picturing history in Alexander Sokurov’s films is to prove that the facet of content and form of this Russian director’s films finds its source in the intention of picturing historic processes occurring throughout the history. Thanks to this Sokurov’s works may be considered not only as an authorial exemplification of film art, but also as the example of philosophy of history discourse, and even the discourse of historiographic (perceived as part of Jörn Rüsen’s historical culture). The author established that the director employs various strategies of picturing the past: of the „witness of his time” (both by depicting subjective authorial perspective and talking about the past from the point of view of an onlooker), of the „archosophist” (shaping the narrative about the past through the prism of archival materials), of the „biographer” (polemicizing with historiographic approach to historical processes), as well as of the narrator of the history (referring to understanding of history in the context of the metaphor).
Strategies of picturing history in Alexander Sokurov’s films
Wydział Filologii Polskiej i Klasycznej
Keywords: Aleksander Sokurow; kinematografia rosyjska; filmoznawstwo; kultura historyczna; historiozofia; Alexander Sokurov; russian cinema; film studies; historical culture; philosophy of history